Newly discovered Early and Middle Bronze Age tombs in Shirak, Armenia - Khachatryan, Hamazasp; Yeganyan, Larisa; Petrosyan, Levon (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The article is dedicated to the study of tomb materials accidentally discovered during excavations in the Shirak region in recent years. The first is the tomb excavated in the area of Azatan village, which is comparable in structure and materials to the complexes of the first stage of the Early Bronze Age, such as the tombs of Talin and Jrvezh, which date back to the third quarter of the 4th millennium BC. The other partially destroyed tomb is located in Ashotsk, the materials of which belong to the Early Kurgan and Trialeti (Tṙełk‘)-Vanadzor cultures. The materials of Azatan tomb are widening our knowledge of the poorly studied Trialeti-Vanadzor culture in Shirak. Of similar significance is the tomb of Aregnadem belonging to the terminal stage of the Trialeti-Vanadzor culture. Thus, the materials of the above-mentioned tombs complement the source basis for the study of different stages of the Early to Middle Bronze Age in Shirak.